1999
DOI: 10.1046/j.1365-2796.1999.00527.x
|View full text |Cite
|
Sign up to set email alerts
|

Heparin‐induced thrombocytopenia (HIT) due to heparin flushes: a report of three cases

Abstract: Abstract. Kadidal VV, Mayo DJ, Horne MK (National Institutes of Health, Bethesda, MD 20892, USA) Heparin-induced thrombocytopenia (HIT) due to heparin flushes: a report of three cases (Case Report). J Intern Med 1999; 246: 325±329.Three cases of heparin-induced thrombocytopenia (HIT) are reported that were provoked by daily heparin flushes of central venous access devices.Each case had confounding features that delayed recognition of the problem. A review of the literature revealed only 29 previously reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(53 citation statements)
references
References 23 publications
0
47
0
1
Order By: Relevance
“…Occasional patients have developed this disorder after exposure to as little as 250 units from a heparin flush (Heeger & Backstrom, 1986). Only a limited number of cases have been described in the literature and the true incidence is unknown (Kadidal, Mayo & Horne, 1999).…”
Section: Literature Available For Reviewmentioning
confidence: 99%
“…Occasional patients have developed this disorder after exposure to as little as 250 units from a heparin flush (Heeger & Backstrom, 1986). Only a limited number of cases have been described in the literature and the true incidence is unknown (Kadidal, Mayo & Horne, 1999).…”
Section: Literature Available For Reviewmentioning
confidence: 99%
“…In the current case, heparin was not used as an anticoagulant for HD; however, daily heparin flushes of dialysis catheters should play a pivotal role in the development of HIT. Indeed, there are several reports of cases of HIT induced by heparin flushes, although the precise frequency with which such conditions lead to HIT remains to be elucidated (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Warkentin (2004a) reorted that HIT was observed in 2.7% of patients treated with subcutaneous UFH injection, but in no patients receiving LMWH; further, thrombotic complications were more frequent in the former group (88.9%) than in the latter (17.8%). Both the bovine/procine UFH and the LMWH data were collected from medical patients receiving LMWH or UFH as "flushes", e.g., oncology patients with indwelling catheters (Mayo et al, 1990;Kadidal et al, 1999). A randomized controlled trial that compared use of porcine UFH with LMWH after hip replacement surgery found that HIT was significantly less common among patients who received the latter treatment (Lee & Warkentin, 2004;Warkentin, 2004a).…”
Section: Epidemiologymentioning
confidence: 99%